2022
DOI: 10.3390/ijerph191912570
|View full text |Cite
|
Sign up to set email alerts
|

The Livelihood of Artisanal and Small-Scale Miners and Awareness of the Use of 3T Minerals in Rwanda—A Case Study in the Rutsiro District: A Qualitative Assessment

Abstract: This article examines the impact of artisanal and small-scale mining (ASM) on livelihood in mining communities in Rwanda (Rutsiro) where wolframite and coltan are mined. The paper discusses the development of ASM and other entrepreneur activities, in particular agriculture. With ASM activities, there is environmental degradation on the one hand but also an improvement in the well-being of the local population on the other. The 3T (tin, tungsten, tantalum) minerals extracted by ASM are used in the electronics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The SSM don't have regular salaries, they have entered into agreement with mine managers to get a certain percentage, usually around 5% of the sales to share among all the workers once a gemstone is found. In contrast to a recent study in Rutsiro, Rwanda [26] average earnings in Mererani were relatively low with the majority of miners on <4.3 USD/day. In the Rwandan study, reported SSM to have not only regular monthly salaries but the salary being relatively good to the extent of attracting workers from other sectors like construction to the mining sector.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The SSM don't have regular salaries, they have entered into agreement with mine managers to get a certain percentage, usually around 5% of the sales to share among all the workers once a gemstone is found. In contrast to a recent study in Rutsiro, Rwanda [26] average earnings in Mererani were relatively low with the majority of miners on <4.3 USD/day. In the Rwandan study, reported SSM to have not only regular monthly salaries but the salary being relatively good to the extent of attracting workers from other sectors like construction to the mining sector.…”
Section: Discussioncontrasting
confidence: 99%
“…In the Rwandan study, reported SSM to have not only regular monthly salaries but the salary being relatively good to the extent of attracting workers from other sectors like construction to the mining sector. Among these SSM interviewed about ill health related to the mining activities, 85% reported dust to be a key challenge, of whom 65% reported silicosis as a major health challenge [26]. While improving workers’ income should be prioritized, this should go hand in hand with improvement of the working environment to ensure the individuals who are rushing in the mines for better paying jobs are in a safe working condition.…”
Section: Discussionmentioning
confidence: 99%